Behaviour photovoltaic panels in Cyprus weather with forced airflow - Giannakou, Konstantinos (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2016)
An experiment has taken place during the summer season, to examine the photovoltaic’s behaviour on efficiency and temperature when air is exerted on the panels by a fan. Several measurements were taken during the summer season which includes morning, midday and afternoon periods. Measurements have been selected to be inserted in the report depending on the appropriateness of the weather. For the experiment, 4 photovoltaic solar panels were used. Τwo monocrystalline silicon solar panels of 10W, (By Bioenergy). SunWare 3061 monocrystlline silicon solar panel of 12W and Sunlinq solar panel of 6.5W which it’s solar cells are from Copper Indium Gallium Diselenide (CIGD) and includes amorphous silicon. The fan used had 3 speed settings and the solar panels are tested for each one. The efficiency of the PV panels have been calaculated for each IV curve graph which are plotted by Strata-sense Wireless IV Curve Tracker. The equation used for calculating the photovoltaic’s efficiency is n = 𝑉𝑚𝑝𝑝 𝑥 𝐼𝑚𝑝𝑝𝐸 𝑥 𝐴. As indicated by the equation, the factors that play a major role for the photovoltaic’s efficiency is the voltage and current at maximum power point, irradiance (E) and area (A) of the panels. The mean temperature of the photovoltaic solar panels was measured by a Lutron Thermometer 947USB which had four thermocouples that were attacthed on solar panels. Also, graphs were plotted of the efficiency against speed of air exerted from fan to observe the behaviour of the PV efficiency as a function of its mean temperature.
Keywords: Photovoltaic solar panels; Copper Indium Gallium Diselenide (CIGD)